Volume 6: Energy Systems: Analysis, Thermodynamics and Sustainability 2007
DOI: 10.1115/imece2007-42332
|View full text |Cite
|
Sign up to set email alerts
|

Observer Design for a Steam Reformer Based Solid Oxide Fuel Cell System With Anode Recirculation

Abstract: In this paper we design an observer for online estimation of species concentrations in a steam reformer based Solid Oxide Fuel Cell (SOFC) system with anode recirculation and with methane as fuel. Since in SOFCs steam reforming occurs both in the reformer and in the fuel cell, a large number of concentration sensors are necessary for accurate control of critical performance variables such as utilization and steam-to-carbon-ratio. The purpose of the observer is to reduce the number of sensors required for contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Das and Mukherjee designed an observer for estimation of species concentrations in an SOFC with a reformer. Steam reforming in SOFCs occurs both in the reformer and in the fuel cell.…”
Section: Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Das and Mukherjee designed an observer for estimation of species concentrations in an SOFC with a reformer. Steam reforming in SOFCs occurs both in the reformer and in the fuel cell.…”
Section: Controlmentioning
confidence: 99%
“…Observers have the capability to dynamically calculate the species concentrations online from available sensor data based on a mathematical model. Das and Mukherjee 133 considered the coupled dynamics of the reformer and the fuel cell. Their study showed that concentrations of all species, all molar flow rates, and all reaction rates can be estimated from measurements of (a) CH 4 and CO concentrations in the reformer and the anode chamber and (b) temperatures and pressures at the reformer and anode exits.…”
Section: Actuators and Sensorsmentioning
confidence: 99%
“…Arcak et al (2004) designed an adaptive observer for hydrogen partial pressure estimation in a PEMFC. Das and Mukherjee (2007) designed an observer for estimation of species concentrations in an SOFC with a reformer. Lin and Hong (2005) presented a sliding-mode state observer to estimate the unmeasurable gas temperatures inside a SOFC from measurements such as that of gas pressure.…”
Section: Fuel Cellsmentioning
confidence: 99%